Implikasi Keperdataan terhadap Risiko dan Tanggung Jawab dalam Perikatan Onlineshop di Tokopedia - Nazlah Aulia; Sri Hadiningrum (Universitas 17 Agustus 1945 Semarang, 2024)
Online shopping transactions through e-commerce platforms such as Tokopedia have become increasingly popular. However, with the growing number of online transactions, there are risks and responsibilities that need to be addressed. This study aims to explore the implications of keperdataan (law relating to civil matters) on the risks and responsibilities in online shop agreements in Tokopedia. The research will focus on analyzing the legal framework that governs online transactions, particularly in terms of consumer protection, contractual obligations, and dispute resolution mechanisms. By examining relevant laws and regulations, as well as case studies of online shop agreements in Tokopedia, the study seeks to identify key legal issues that may arise in online transactions and provide recommendations for both consumers and online sellers.